Synthesis, Structural Analysis and Screening of Some Novel 5-Substituted Aryl/Aralkyl-1,3,4-Oxadiazol-2-Yl 4-(Morpholin-4-Ylsulfonyl)Benzyl Sulfides as Potential Antibacterial Agents - Akhtar, Muhammad Nadeem; Rehman, Aziz-ur; Gul, Samreen; Abbasi, Muhammad Athar; Nafeesa, Khadija; Ahmad, Irshad; Afzal, Saira (Taylor & Francis, 2015)
A series of new 5-substituted aryl/aralkyl-1,3,4-oxadiazol-2-yl 4-(morpholin-4-ylsulfonyl)benzyl sulfides 6a-k were synthesized by converting multifarious aryl/aralkyl organic acids 1a-k successively into corresponding esters 2a-k, hydrazides 3a-k and 5-substituted aryl/aralkyl-1,3,4-oxadiazole-2-thiols 4a-k. Finally, the target compounds, 6a-k were prepared by stirring 5-substituted-1,3,4-oxadiazole-2-thiols with 4-(4-(bromomethyl)phenylsulfonyl) morpholine (5) in the presence of N,N-dimethylformamide (DMF) and sodium hydride (NaH). The structures of the newly synthesized compounds were elucidated by spectroscopic techniques. In addition, the anti-bacterial activity of all the synthesized compounds was investigated in vitro against Gram-positive and Gram-negative bacteria by using ciprofloxacin as reference standard drug and the results showed that some of the tested compounds possessed good anti-bacterial activity.